A survey of owner attitudes and experiences in managing diabetic dogs - Aptekmann, Karina P. [UNESP]; Schwartz, Denise S. (Elsevier, 2011)
A survey of the experiences of owners of diabetic dogs was carried out by distributing questionnaires to veterinary clinics in São Paulo, Brazil. A total of 93 dog owners were surveyed over a 4. month period and descriptive statistical analysis, frequency distribution and correlations were performed. In most cases the clinical condition of the dogs had improved following treatment and owners were largely satisfied with veterinary intervention. Injection of neutral protamine hagedorm twice daily was the most commonly prescribed treatment and respondents found this procedure easy to perform, although it did pose some difficulties when the owners were away from their animals. Cost was considered an important factor at the initiation of treatment programs. The information gleaned from this survey, in providing useful insights into the attitudes and experiences of owners of diabetic animals, will contribute to improvements in the treatment and management of such patients. © 2011 Elsevier Ltd.
Keywords: Canine; Diabetes; Owners; Questionnaire; Survey; caninsulin; insulin; insulin glargine; isophane insulin; pig insulin; unclassified drug; vetinsulin; animal care; animal experiment; attitude; Brazil; diabetes mellitus; diet therapy; dog disease; exercise; health care cost; human; nonhuman; pet animal; questionnaire; veterinary medicine; Animals; Attitude to Health; Cost of Illness; Diabetes Mellitus; Dog Diseases; Dogs; Hypoglycemic Agents; Questionnaires; Animalia; Canis familiaris